1977
DOI: 10.1136/ard.36.6.508
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Libman-Sacks endocarditis. Assessment by light and immunofluorescent microscopy in two patients.

Abstract: SUMMARY The possible contribution of immunological mechanisms in the development of LibmanSacks endocarditis was studied in 2 patients with systemic lupus erythematosus who underwent aortic valve replacement. Sections of verrucous lesions, stained with haematoxylin and eosin, showed three apparently distinct zones: an outer exudative zone of fibrin, nuclear debris, and haematoxylin-stainbd bodies; a middle organizing zone of proliferating capillaries and fibroblasts; and an inner zone of neovascularization whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(15 citation statements)
references
References 26 publications
0
13
0
2
Order By: Relevance
“…Inflammation is usually noted with infiltration of mononuclear cells [10]. Immunofluorescent microscopy has also revealed deposition of immunoglobulins and complement [33]. In examining the immunopathology of heart valves from autopsy patients with primary and secondary (due to SLE) APS, a study by Ziporen et al [34] found the presence of anticardiolipin in immunoglobulin deposits eluted from the valve tissue, lending further evidence to the association between APS and LS endocarditis.…”
Section: Pathologymentioning
confidence: 96%
“…Inflammation is usually noted with infiltration of mononuclear cells [10]. Immunofluorescent microscopy has also revealed deposition of immunoglobulins and complement [33]. In examining the immunopathology of heart valves from autopsy patients with primary and secondary (due to SLE) APS, a study by Ziporen et al [34] found the presence of anticardiolipin in immunoglobulin deposits eluted from the valve tissue, lending further evidence to the association between APS and LS endocarditis.…”
Section: Pathologymentioning
confidence: 96%
“…In subsequent studies in SLE patients, the presence of heart valve disease was associated with aPL [5,6]. This association was further supported by histological findings of fibrin strands and vasculopathy of the proliferating capillaries in valvular vegetations in patients with SLE and/or APS [7,8]. The subsequent reports were heterogeneous in terms of design, with some of them focusing clearly on the structural abnormalities of the valves either in SLE (with or without aPL) [9][10][11] or APS [12][13][14] and others emphasizing the functional disturbances of the myocardium in these patients [15][16][17][18].…”
Section: Introductionmentioning
confidence: 77%
“…Immunofluorescence shows immunoglobulins and complement deposition in the junctional vessels in the inner layer of neovascularization. 5,18 Most of the patients with LibmanSacks vegetations have accompanying leaflet fibrosis with valve thickening. 1…”
Section: Pathology and Pathophysiologymentioning
confidence: 99%